Changing trends in modes of delivery in the dublin maternity hospitals over a decade. (18th April 2012) - Vaughan, DA; Sarkar, RK; Coulter-Smith, S; Robson, M; Fitzpatrick, C
Abstract : Objective: To describe the changing trends in modes of delivery, in a single large urban Irish population over the past 10 years. Study design: A retrospective review of the modes of all deliveries in the three Dublin Maternity Hospitals from 1999 to 2009 was performed. The annual rates of spontaneous vaginal delivery, forceps, ventouse deliveries, and caesarean section in the three hospitals were calculated. The rates of the different modes of delivery were then analysed to ascertain if a trend existed. Results: During the 10 year study period there were a total of 255, 295 deliveries. During this time period the caesarean section rate has increased from 16.98% (n=3681) in 1999 to 24.4% (n=6480) in 2009 (p<0.05). The operative vaginal delivery rate, has increased from 13.5% in 1999 to 17.4% in 2009. The rate of forceps delivery has remained relatively unchanged (5.34% in 1999 vs 5.87% in 2009), while the ventouse delivery rate has increased significantly from 8.16% (n=1770) in 1999 to 11.54% (n=3063) in 2009. Of note, the rate of spontaneous vaginal delivery has decreased significantly over the past 10 years from 69.5% (n=15, 072) to 58.17% (n=15, 440) in 2009. Conclusion: Obstetrics over the past 10 years in the Dublin Maternity Hospitals has seen a dramatic increase in the Caesarean section rate and a lesser increase in the overall operative vaginal delivery (rate. This has led to a consequent significant decrease in the spontaneous vaginal delivery rate. The reasons for the increase in caesarean section rate in our cohort are multifactorial.